Effects of water-soluble antioxidants and MAPKK/MEK inhibitor on curcumin-induced apoptosis in HL-60 human leukemic cells - Ratana Banjerdpongchai (2018)
Curcumin is the main biologically active phytochemical compound in turmeric. It has been shown to have anticarcinogenic activity. The aims of the study were to identify the mechanism of apoptosis of HL-60 human promyelocytic leukemic cells induced by curcumin and to determine the effects of water-soluble antioxidants, ascorbic acid, Trolox (a water-soluble form of vitamin E), glutathione (GSH) and N-acetylcysteine (NAC) on this process. HL-60 cells were incubated with curcumin for 24 h and apoptotic cells were quantitated by flow cytometry following staining with annexin V-FITC and propidium iodide. Curcumin-treated HL-60 cells produced reactive oxygen species as detected by the dichlorofluorescein fluorescent assay. Apoptosis occurred via the mitochondria pathway as curcumin reduced mitochondrial membrane potential in a dose-dependent manner. In the presence of 10 μM curcumin, vitamin C (56 nM - 5.6 μM) inhibited apoptosis of HL-60 cells; GSH at low concentration (1 μM) reduced apoptosis but had no effect at higher concentrations (10, 100 μM); and Trolox and NAC at 10 and 100 μM, respectively, enhanced apoptosis, but this effect was abolished at higher concentration (1 mM) of NAC. MAPKK/MEK inhibitor PD98059, enhanced curcumin-induced HL-60 apoptotic cell death.